Association between Body Mass Index and Short-Term Clinical Outcomes in Critically Ill Patients with Sepsis: A Real-World Study. (15th October 2020) - Lin, Shan; Ge, Shanhui; He, Wanmei; Zeng, Mian
Abstract : Background . Obesity is now recognized as one of the major public health threats, especially for patients with a critical illness. However, studies regarding whether and how body mass index (BMI) affects clinical outcomes in patients with sepsis are still scarce and controversial. The aim of our study was to determine the effect of BMI on critically ill patients with sepsis. Materials and Methods . We performed this study using data from the Medical Information Center for Intensive Care III database. A multivariate Cox regression model was used to assess the independent association of BMI with the primary outcome. Results . A total of 7, 967 patients were enrolled in this study. Firstly, we found that the 28-day mortality was reduced by 22% (HR = 0.78, 95% CI 0.69–0.88) and 13% (HR = 0.87, 95% CI 0.78–0.98) for obese and overweight compared to normal weight, respectively. Subsequently, a U-shaped association of BMI with 28-day mortality was observed in sepsis patients, with the lowest 28-day mortality at the BMI range of 30–40 kg/m 2 . Finally, significant interactions were observed only for sex (P = 0.0071 ). Male patients with a BMI of 25-30 kg/m 2 (HR = 0.74, 95% CI 0.63–0.86) and 30-40 kg/m 2 (HR = 0.63, 95% CI 0.53–0.76) had a significantly lower risk of 28-day mortality. Conclusions . A U-shaped association of BMI with 28-day mortality in critically ill sepsis patients was found, with the lowest 28-day mortality at a BMI range of 30–40 kg/m 2 . Notably, male patients were protected by a higher BMI more effectively than female patients as males had a significantly lower mortality risk.